C1–C2 fusion with absence of C1 posterior arch and presence of C2 high-riding vertebral artery: Is it possible? - Wong, Tat Seng; Abdul Rashid, Muhammad Lutfi; Hasan, Mohd Shahnaz; Chiu, Chee Kidd; Chan, Chris Yin Wei; Kwan, Mun Keong (SAGE Publications (UK and US), 2019)
The presence of anatomical anomalies such as absence of C1 posterior arch and presence of C2 high-riding vertebral artery may not allow a conventional C1–C2 fusion, and this patient will require occipitocervical fusion. A 62-year-old lady presented with cervical myelopathy. CT scan demonstrated an os odontoideum with C1–C2 dislocation. The posterior arch of atlas on right C1 vertebra was absent, and there was high-riding vertebral artery on left C2. MRI revealed severe cord compression with cord oedema. The chronic atlantoaxial dislocation was reduced successfully with skeletal traction. Hybrid C1–C2 fusion augmented with autogenous local bone graft with corticocancellous iliac crest bone graft was performed to avoid an unnecessary occipitocervical fusion. She was stable throughout surgery and discharged 6 days later. CT scan 6 months post-operation showed a solid posterior fusion mass. Hybrid C1–C2 fusion can be performed to avoid occipitocervical fusion despite presence of abnormal anatomy at C1 and C2 vertebrae. © The Author(s) 2019.